The Role of Quality Health Information at Hospitals in Relation to Health Information Technology: The Impact of HIT Adoption on Quality of Care in Saudi Hospitals (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Recent efforts have focused heavily on promoting HIT's usage to improve healthcare quality.However, there is still a lack of knowledge on how HIT adoption affects the quality of care provided topatients in hospitals. With this research, we aimed to learn how different HITs correlate with QI practicesand tactics, POC adherence, risk-adjusted in-hospital mortality, patient satisfaction, and the perceptionsof hospital quality managers and frontline physicians. In this study, we investigate how the adoption ofHIT in Saudi hospitals affects the quality of patient care.